Efforts to Increase Teacher Creativity in Motivating Student Learning - Rusliana, Helena (Jurnal Ilmiah Mandala Education (JIME), 2024)
In increase quality education, must there is continuity performance and quality improvement. Continuous quality improvement serves as a measure for resolve problem education quality low which depend on approach conventional. this writing study about deep teacher creativity motivating study participant educate . Teacher creativity in motivating Participant educate is also part from Behavior Educational Organization , which is behavior a teacher gives influence good for development participant he taught . Study is a marked process with exists change in self somebody good knowledge , understanding , attitudes and behavior he did nor his skills . Participant students really need motivation and encouragement in study , encouragement from in nor from outside . If participant educate have motivation strong study , then _ Theory lesson will light and easy as well as the learning process Becomes fun . Teacher creativity is one _ pusher motivation learn . Creative teacher could develop ability of new ideas and ways new in teach . Teacher creativity can be in the form of creativity in classroom management and the use of learning media. Ways to generate motivation that teachers can do include giving numbers, prizes, competition, ego involvement, tests, knowing results, praise, punishment, desire to learn, interest, and recognized goals.